Using Multiple-Mini-Interviews for Admission into Teacher Education - Salingré, Barbara; MacMath, Sheryl (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
This article reports on the validity of the Multiple-Mini-Interview (MMI) method as it was used by a post-degree teacher education program as part of their admissions process to select candidates for entry into the program. The MMI, primarily used for medical school admittance, involves several stations with different interviewers. Comparisons were made between the MMI, other intake variables, and outtake measures. Quantitative analyses also examined possible interviewer, station, gender, and heritage effects. Results support the claim that the MMI can be used to measure dispositions not measured by other intake variables; however, some concerns did emerge.